Analisis Pendidikan Non Formal Komunitas San’t Egidio pada Anak Pemulung di Kampung Pemulung Blok O Yogyakarta - Rufina Nenitriana S. Bete; Handrianus Akoit; Roy Gustaf Tupen Ama (Lembaga Pengembangan Kinerja Dosen, 2025)
Until now, scavenger children are still often underestimated because of their various problems, including education. In fact, in accordance with the concept of lifelong learning, there is no such thing as too young, too old, anywhere, anytime, and anyone, including children of scavengers, can learn. This research aims to determine the extent of the implementation of non-formal education services by the San't Egidio community to realize lifelong learning for scavenger children in Block 0 Yogyakarta. The method used in this research is qualitative with descriptive analysis. Data collection through observation and interviews. The subjects in this research were scavenger children who attended non-formal education and the informant subjects were parents and members of the San't Egidio community. This research resulted in the finding that the non-formal education services provided by members of the San't Egidio community were in the form of tutoring for scavenger children. By providing tutoring, scavenger children become accustomed to learning, and can develop their knowledge and creativity.